PENDAMPINGAN PENYUSUNAN BAHAN AJAR PJOK BERBASIS ONLINE BAGI KKG PENJAS SD KECAMATAN HAMPARAN PERAK - Rahma - Dewi; Imran - Akhmad; Amir - Supriadi; Nurkadri - - (Universitas Negeri Medan, 2021)
The partner of the Assisted Village Program is the Education Office of the Technical Implementation Unit (UPT) of Hamparan Perak Subdistrict, which is one of the districts in Deli Serdang which is focused on the Primary School Physical Education Teacher KKG. There are several problems with partners, including (1) Lack of users of technology as a learning resource. (2) Teachers are less able to take advantage of technological developments in designing online-based teaching materials. (3) PJOK teachers tend to use less technology in designing a lesson because they are not able to use technology. Of the three main problems, it is not possible to solve the three problems, so in this KKG Physical Education Learning Quality Improvement activity, priority issues will be resolved with partners in this activity, namely: 1) increasing the knowledge and skills of partners regarding making online-based teaching materials, 2 ) provide facilities for the preparation of online-based teaching materials for partners, 3) train partners to be able to use online-based teaching materials and be able to make teaching materials independently. 4) Making online-based teaching materials as a creative way to find learning resources for PKM partners. The expected result in PKM activities is the development of a partner team with increased abilities in designing new online-based teaching materials and can be an example for other areas in terms of developing learning in accordance with the era of the industrial revolution 4.0. with online application-based product goods.The method that will be used to achieve the goals of community service activities is, Improving the Quality of Learning KKG Physical Education is an empowerment model with the following steps: 1) Preparation stage; 2) Assessment Phase; 3) Planning Phase Alternative Programs or Activities; 4) Action Plan Formulation Phase; 5) Implementation Stage (Implementation) of Programs or Activities; 6) Evaluation Phase; and 7) Termination Stage. The implementation of the Physical Education KKG Learning Quality Improvement program will be carried out as an effort to empower the PJOK Primary School Teacher Working Group in partner areas. Keywords: teaching materials, based, online,